Stabilization and Crystal Characterization of Electric Arc Furnace Oxidizing Slag Modified with Ladle Furnace Slag and Alumina - Chia-Chun Li; Chi-Ming Lin; Yu-En Chang; Wei-Ti Chang; Weite Wu (Metals, 2020)
Ladle furnace slag (LFS) is a by-product of a steel plant. As the chemical composition and free lime (f-CaO) content of each batch of slag are significantly different, it is difficult to use the same operation method to recover LFS. In this study, three types of LFS were used to partially replace lime in the dephosphorization process, and the compositions were adjusted to a fixed range by adding Al2O3. This method reduced the effect of different LFS components and significantly reduced the Ca2SiO4 amount (from 31.4% to 17.1%) in the produced modified oxidizing slag. Furthermore, after dephosphorization, the X-ray diffraction (XRD) patterns of the three LFSs indicated transformation into gehlenite and wustite. The modified oxidizing slag f-CaO content was 0.41%, which was lower than that in the electric arc furnace oxidizing slag (1.2–1.4%) and the LFS (0.9–3.4%). In addition, the expansion test results of the modified oxidizing slag showed almost no expansion, which conforms to the ASTM D2940 standards; thus, this material can be used for preparing paving materials. This study provides an approach for LFS treatment that could reduce costs within the steel industry.